PENGEMBANGAN HANDOUT BIOLOGI BERBASIS PENDEKATAN SPIRITUAL PADA MATERI SISTEM REPRODUKSI MANUSIA UNTUK MTsN - Fadri, Rahmira; Indriati, Gustina; Fadilah, Muhyiatul (STKIP PGRI Sumbar, 2014)
ABSTRACT Biology instructional materials used by students MTsN Batukambing is textbook. The use of textbooks is not optimaly to assist students in learning, because textbooks loaned from the school library and only be used in the learning process at school. As a result, students find it difficult to learn the lessons at home. In addition, book is less attractive, the images presented in black and white, and not integrated with religious education. In learning about human reproductive system material students tend not focus and think negatively. It is needed a spiritual approach in textbook by integrated in to subject matter with religious education. To assist students in the learning process it is needed to develop teaching materials in the form of handouts. This study aims to determine the validity and practicality handouts spiritual approach based on biological material of human reproductive system to MTsN. This is the development research use 4D models consists of4 stages, define, design, develop and disseminate, but this study is limited to develop stages. This type of research data is the primary data consists of the results of the validity and practicality. This study was conducted on 3 April 2014 at MTsN Batukambing. Validity testing results that this handout is very valid criteria with an average value of 90.15 %. Practicality testing by teacher informed that this handout is practical criteria with an average value of 80.67 % and the practicality of testing by students informed that this handout is very practical criteria with an average value of 90.61 %. It can be concluded that the handouts biology based spiritual approach in human reproductive system in MTsN produced very valid and very practical .